A Market–Climate Change Model for Weather-Sensitive Sectors: Moving Average Approaches - Vlady, Svetlana (Journal of Strategic Innovation and Sustainability, 2019)
The weather has become more unpredictable and unseasonal. In Australia, weather-sensitive sectors are the key players in the economy. The main objective of this research is to raise awareness of environmental issues in investment decisions and develop a new Market–Climate Change Model. The Moving Average (MA), the Exponential Moving Average (EMA), and the Auto-Regressive Integrated Moving Average (ARIMA) techniques have been used to test a model. The results of this study indicate that weather-related variables influence the investment returns of weather-sensitive companies and should be included in the market model to support sound investment decisions.